Maskulinitas dan Pandemi COVID-19: Studi Kasus Pakistan - Dias Pabyantara Swandita Mahayasa; Anggi Koenjaini Putri (Universitas Airlangga, 2020)
This research aims to elaborate on the question of why male patientsof COVID-19 dominating globally (data are taken per 24 June 2020).Depart from the hegemonic masculinity concept, the argument proposedin this writing is that traditional gender role which positioned men asbreadwinner is one of the vital factors to the high infection among men.Men who are supposed to work outside their house is arguably morevulnerable to the virus. The argument is extracted from both Pakistanexperience against COVID-19. According to UN Women, this country oftop the list of countries who has the highest disparity among male andfemale patient, reaching more than 70 percent of male and 30 percent forthe female. The statistic goes hand in hand with the notion of traditionalgender roles rooted deep within the community.